Family quality of life with childhood sickle cell in Oman - Al Jabri, Wafa (KHD-Production, 2025)
Managing a child with sickle cell disease (SCD) can be challenging for the family. This study investigates the quality of family life in families of children with SCD in Oman, a relatively recent and diverse topic, particularly in the Middle Eastern context. Through a cross-sectional design, 103 Omani mothers of children with SCD were surveyed to explore their perceptions of FQOL and identify factors influencing it using the Beach Center FQOL scale. The research study found that mothers generally perceived FQOL as high, with the highest satisfaction in physical/material well-being and the least in emotional well-being. This research study identified significant differences in FQOL among different family structures, with nuclear families reporting higher FQOL than families of single-parent or polygamous structures. Content analysis of open-ended responses provided suggestions for improving healthcare services, providing financial aid, and advocating for special considerations. The findings highlight the necessity of interventions targeted at providing support and assistance to families with SCD, especially those in polygamous structures. Additionally, the study underscores the need for further research in this area, considering the current study's limitations, and highlights the importance of designing FQOL assessment tools for healthcare institutions for families of children with SCD and other chronic conditions.